Epidemiology and Pathogenesis of Coronavirus Disease (COVID-19) - Ram Bahadur Khadka; Ravin Bhandari; Rabin Gyawali; Balram Neupane; Dhakaraj Pant (Novel Research in Microbiology Journal, 2020)
An acute respiratory syndrome (ARDS) episode was first identified in Wuhan, China, and later officially designated as COVID-19 by the WHO. It is caused by SARS-CoV-2 that is likely associated with zoonotic transmission. Based on the live data from live reference website Worldometer which provides counters and realtime statistics for diverse topics data, COVID-19 has influenced 186 nations. China reported 25% of cases, while 75% of the remaining cases were reported in other nations. The clinical and genetic characteristics of SARSCoV-2 support the similar pathogenesis pattern between SARS-CoV and MERS-CoV. The elevated level of cytokine release during the infection caused the failure of multiple organs leading to the patient death. Treatment of patients depends on the clinical course and symptoms associated with the COVID-19. Several prevention and control measures including; active surveillance, use of masks, and hand sanitizers are recommended to stop the spread of this virus. Besides, COVID-19 was sampled using a throat swab to detect the viral nucleic acid using Real Time Polymerase Chain Reaction (RT-PCR), for early detection and treatments evaluation. In this review, we comprehensively summarized the COVID-19 epidemiology, pathogenesis and diagnosis, using suitable literatures obtained from reliable sources.